High-Performance Thin-Layer Chromatographic Fingerprints of Triterpenoids for Distinguishing Between Isodon lophanthoides and Isodon lophanthoides var. gerardianus. (23rd November 2019) - Lin, Chaozhan; Liu, Fangle; Zhang, Runjing; Liu, Meiting; Zhu, Chenchen; Zhao, Jing; Li, Shaoping
Abstract: Background: The aerial parts of Isodon lophanthoides (Buch. Ham. ex D. Don) Hara (IL) has been officially recorded as Isodonis lophanthoidis herba by many provincial quality control standards for Chinese herbal medicines in China. Recently, it has been found that one of its varieties, I. lophanthoides var. gerardianus (Benth.) Hara (ILVG) was pretended to be I. lophanthoidis herba in herbal material markets or cultivated bases. Because of the similarity on appearance, these two close-related species were difficult to be identified by morphological characters, especially when they are dried and sliced. Objective: To establish a rapid and specific method for identification of the two herbal medicines. Method: In this paper, a fingerprint of triterpenoids by HPTLC coupled with a digital profiling was established to identify IL and distinguish it from its substitute, ILVG. The specific HPTLC fingerprints constructed by determining twelve batches of IL samples and thirteen batches of ILVG samples, intuitionally reflected the difference between the two species on HPTLC image and the peak-peak rations of chemical distribution. Results: Authentication results of nine batches of commercial samples by the above established HPTLC fingerprints exhibited coincident conclusion with that by morphological means. Conclusions: The HPTLC fingerprint is proven to be simple, repeatable, specific, and suitable for rapid identification of I. lophanthoidis herba . Highlights: An efficient method for identification and distinguishing Isodon lophanthoides from its substitute, I. lophanthoides var. gerardianus, was established. HPTLC fingerprints of ursane-type triterpenoides were constructed and validated by determining IL and ILVG samples.